1983
DOI: 10.3133/ofr83423
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Geological Survey-Ingeominas mineral resource assessment of Colombia; ore deposit models

Abstract: This compendium of ore deposits models was assembled for the Colombia Mineral Resource Assessment Project. The objectives of the compendium are: (1) to define mineral deposit types so that all project members have a common vocabulary or deposit classification scheme to which mineral occurrences, favorable geologic environments, favorable geochemical anomalies, and tonnage-grade models may be related; (2) to provide data on the environments of ore deposition so that favorable rocks, structures, and tectonic set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…This suggest the same mantle source ;2-The LREE / HREE ratio of Tertiary basalt are similar but lower than that of Abu Darag Early Cretaceous basalt . [26] found that the high field strength element ratios remain unmodified for basalts of the same mantle source; [27] . The continental crust of Egypt is thinner in the northern part [3].This may explain the oceanic affinity of some Tertiary basalt in the northern part of Egypt and may be related to Red Sea opining, 5-The chemical weathering has increased LOI, MgO and K 2 O and decreased CaO from the marginal part of Abu Darag basaltic dyke, upper part of Abu Zenima flow and Ehamer dyke, resulting in modified major element compositions.…”
Section: Nomenclature Magma Type and Tectonic Settingmentioning
confidence: 99%
“…This suggest the same mantle source ;2-The LREE / HREE ratio of Tertiary basalt are similar but lower than that of Abu Darag Early Cretaceous basalt . [26] found that the high field strength element ratios remain unmodified for basalts of the same mantle source; [27] . The continental crust of Egypt is thinner in the northern part [3].This may explain the oceanic affinity of some Tertiary basalt in the northern part of Egypt and may be related to Red Sea opining, 5-The chemical weathering has increased LOI, MgO and K 2 O and decreased CaO from the marginal part of Abu Darag basaltic dyke, upper part of Abu Zenima flow and Ehamer dyke, resulting in modified major element compositions.…”
Section: Nomenclature Magma Type and Tectonic Settingmentioning
confidence: 99%
“…The study area is situated in the Sierra Nevada physiographic province, which contains the largest concentration of tungsten deposits in the United States (Newberry, 1982). The mineral-deposit model that is most appropriate to apply in this study area is the tungsten-skarn felsic-plutonic-rock model (Einaudi and others, 1981;Cox, 1983;Cox and Singer, 1986). Tungsten skam deposits form along contacts and in roof pendants of batholiths and in thermal aureoles of apical zones of stocks that intrude carbonate rocks.…”
Section: Mineral Resource Potentialmentioning
confidence: 99%
“…La presente forma de los modelos descriptivos en una pagina se elaboro por Dennis Cox, Donald Singer y Byron Berger y el metodo grafico para presentar los dates de ley y tonelaje se realize por Donald Singer. En el proyecto colombiano se utilizaron 65 modelos descriptivos (Cox, 1983a y b) y 37 modelos de ley-tonelaje (Singer y Mosier, 1983a y b).…”
Section: Prepack)unclassified